Integration of Cloud Services in Support to Tests, Simulations and Knowledge Dissemination with Cluster Environments - Juliani, Felipe; Barbosa, Jonathan; Mury, Antônio Roberto; Schulze, Bruno (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
In this paper is presented a computing platform for use of cluster environments. This platform integrates the cloud middleware services with an application for specifying these clusters and tasks submissions to the same. The provision of resources is expanded with the availability of completely different environments acting on the same infrastructure. Thus, it is possible better meet the specific necessities of each user, contributing with the focus of the studies and researches.